Evolution Law of Adsorption and Desorption Characteristics of CH4 in Coal Masses during Coalbed Methane Extraction - Tang, Z.; Yang, S.; Xu, Guang; Sharifzadeh, Mostafa; Zhai, C. (American Chemical Society, 2018)
The low-temperature oxidation of coal during coalbed methane extraction is inevitable. To study the evolution of the CH4 adsorption and desorption characteristics in coal masses during the low-temperature oxidation of coal, starting from the evolution of physical and chemical adsorption of CH4 in coal masses during the low-temperature oxidation of coal and combining it with the evolution of free radicals, we constructed a physical model of CH4 adsorption and desorption in the coalbed methane extraction process. This model provides the theoretical basis for improving the efficiency and quantity of coalbed methane extraction. Our results indicate that during coalbed methane extraction, the mesopores, macropores, and overall porosity increase with the rise in oxidation temperature. However, the number of micropores first increases and then decreases during the process, leading to the CH4 physical adsorption capacity showing a trend of first increasing and then decreasing with increasing oxidation temperature; however, the number of -COOH groups shows the opposite trend to that of the number of micropores, resulting in the CH4 chemical adsorption capacity first decreasing and then increasing with the increase of the oxidation temperature; meanwhile, the free radical content increases gradually with the increasing oxidation temperature, leading to the continuous consumption of O2 adsorbed on the coal surface and the reinforcement of the CH4 adsorption capacity. To maximize coalbed methane extraction efficiency, it is necessary to take measures to avoid the low-temperature oxidation of coal at the initial stage.